IMPLEMENTASI SISTEM MONITORING SERTA KONTROL DEBIT DAN LEVEL PENAMPUNG AIR BERBASIS APLIKASI ANDROID DI PT. TELKOM PROPERTY - suyetno, Muhammad effendI; Widagda, Mikail Eko Prasetyo; Hilmansyah, Hilmansyah (Teknik Elektro Politeknik Negeri Balikapapan, 2025)
Research along with the times made a water storage area that is used as a reserve of clean water in case of disturbances that cause water scarcity to occur. Disruption of clean water can be caused by several reasons, for example, a clean water management company that is experiencing disruptions so that there is no water supply at home. This is where the water storage function is used. There are problems that arise when the water level in the water reservoir is not known, it is possible that overflow or empty water conditions can occur due to a lack of control over the water reservoir, so it is necessary to make a tool that can control and monitor the filling of water reservoirs based on the Internet of Things with android application so that control can be done remotely. From this problem, the author makes a monitoring system for controlling and controlling water levels and water discharge based on an Android application by using the JSN SR04T ultrasonic waterpoof sensor as a water level gauge and also using a water flow meter sensor to measure the discharge from the tap to the water reservoir if the water volume will be full there will be application display to close the faucet using the solenoid valve as an output.